Pengaruh Daya Tarik Wisata, Pengalaman Wisatawan, dan Kepuasan Wisatawan Terhadap Minat Berkunjung Kembali pada Punthuk Setumbu - Nasirudin, Hikmawan; Subarjo, Subarjo (Journal of Humanities Education Management Accounting and Transportation, 2025)
This study aims to analyze the influence of tourist attractions, tourist experiences, and tourist satisfaction on the intention to revisit Punthuk Setumbu. This study was conducted using a quantitative approach with a questionnaire as a data collection tool. The results of the instrument test stated that the data in this study were proven to be valid and reliable. The results of the classical assumption test stated that the data in this study were normally distributed and produced a regression model that was free from multicollinearity and heteroscedasticity. The results of this study prove that: (1) tourist attractions have a positive and significant effect on the intention to revisit Punthuk Setumbu, (2) experience has a positive and significant effect on the intention to revisit Punthuk Setumbu, (3) tourist satisfaction has a positive and significant effect on the intention to revisit Punthuk Setumbu, (4) tourist attractions, tourist experiences, and tourist satisfaction simultaneously affect the intention to revisit Punthuk Setumbu, Magelang.